PREPARATION FOR THE CPA EXAMINATION–THE UNIVERSITY OF ALABAMA CPA REVIEW COURSE. - Van Voorhis, Robert H. (The Accounting Review, 1956)
Abstract Considerable attention has been given in recent years to the preparation of candidates for the CPA examination. A recent and comprehensive part of the studies have been made and others are in process, which cover far more cues and hence give results, which may be more significant statistically as to the experience of CPA candidates in general. But it seems worth noting that of 186 persons who have taken one or more sections of the Alabama CPA Review Course, and whose present addresses are known, it is certain that 115 are now CPAs, while the status of forty is unknown. Of the 136 who returned the questionnaire, a total of 105 are CPA's. This is not to imply that those who succeeded did so entirely because of the review course. However, many students have given the course credit for providing that final boost which may often make just the difference that leads to a passing grade. The course is not a panacea guaranteed to get all and sundry through the CPA examination. However, it has proved to be most worthwhile for serious candidates who have already prepared themselves as well as they can through college courses, correspondence courses, or in other ways, and who still need a final lift to help them through.